2015
DOI: 10.1083/jcb.201505119
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor–retinoid X receptor heterodimer signaling regulates oligodendrocyte progenitor cell differentiation

Abstract: Activation of retinoid X receptor γ and vitamin D receptor (VDR) heterodimer via vitamin D enhances oligodendrocyte progenitor differentiation, whereas blocking VDR impairs differentiation and myelination ex vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 61 publications
(41 reference statements)
1
47
0
1
Order By: Relevance
“…In general, NFATC2 is believed to induce transcription, but multiple reports indicate a function as transcriptional repressor as well (Ranger et al 2000;Baksh et al 2002;Carvalho et al 2007;Baumgart et al 2012). And finally, RXRG is a member of the ligand-responsive transcription factor family of retinoic acid/X receptors and is able to activate a variety of cellular processes, depending on its partner nuclear receptor in the DNA-binding heterodimer complex (Altucci et al 2007; de la Fuente et al 2015). It promotes the dedifferentiation and invasion of tumor cells Papi et al 2010) and has been shown to be involved in minimal residual disease of melanoma (Rambow et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In general, NFATC2 is believed to induce transcription, but multiple reports indicate a function as transcriptional repressor as well (Ranger et al 2000;Baksh et al 2002;Carvalho et al 2007;Baumgart et al 2012). And finally, RXRG is a member of the ligand-responsive transcription factor family of retinoic acid/X receptors and is able to activate a variety of cellular processes, depending on its partner nuclear receptor in the DNA-binding heterodimer complex (Altucci et al 2007; de la Fuente et al 2015). It promotes the dedifferentiation and invasion of tumor cells Papi et al 2010) and has been shown to be involved in minimal residual disease of melanoma (Rambow et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…OPCs were isolated by shaking off loosely adherent cells from the astrocyte adherent cell monolayer. The supernatant (enriched in OPCs) was collected and microglial cells were removed by incubation in plastic Corning petri dishes (BD, Oxford, UK) 15 min at 37 C. As previously described, this procedure results in a relatively pure population of OPCs (de la Fuente et al, 2015). Indeed, we determined that 92 ± 4% of total cells were Olig2-expressing undifferentiated OPCs.…”
Section: Opcs Culturesmentioning
confidence: 99%
“…Interestingly, two of the aforementioned transcriptional hubs, RXRA-NR1H3 complex and SREBF1, have been previously described as master regulators of lipid synthesis in mammary epithelial cells6162, corroborating our results. Among the remaining hubs, MXI1, NFE2, RXRA-VDR and RAD21 have known role in cell differentiation63646566. To the best of our knowledge, RFX5 does not have any previously known association with BC cell differentiation.…”
Section: Resultsmentioning
confidence: 81%